PENGARUH MEDIA PEMBELAJARAN SPINNING WHEEL TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS 5 MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI SEKOLAH DASAR NEGERI (SDN) PANANCANGAN 4 KOTA SERANG - Khanzani, Citra Layisa; Umalihayati; Aini, Syarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low effectiveness of science teaching at the elementary school level due to the minimal use of technology-based media. The research aimed to analyze the effect of Spinning Wheel as an instructional medium on the learning outcomes of fifth-grade students at SDN Panancangan 4, Serang City. A quantitative pre-experimental method with a One Group Pretest-Posttest Design was employed. The instruments consisted of a learning achievement test (25 multiple-choice and 5 essay items) and a student response questionnaire. Data were analyzed using prerequisite tests, the Wilcoxon Signed Rank Test, and descriptive statistics. The findings showed that the average pretest score was 45.17 and the posttest score was 84.89, with minimum–maximum values of 24.00–62.00 and 70.00–97.00, respectively. The Wilcoxon test revealed a significance value of 0.000 (<0.05), indicating a significant effect of the Spinning Wheel on improving student learning outcomes. In addition, student responses toward the use of this medium were positive, reflected in higher motivation, focus, and active participation during lessons. These results suggest that the Spinning Wheel is effective as an interactive medium that not only enhances academic achievement but also fosters a more engaging and enjoyable learning atmosphere. Therefore, the application of simple technology-based media such as the Spinning Wheel can serve as an alternative strategy for teachers to optimize science learning outcomes in elementary schools.